2021
DOI: 10.13073/fpj-d-20-00030
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Bamboo Part Sorting System Design via Machine Vision

Abstract: The defect rate of initially produced block bamboo (Bambusoideae) parts is >20 percent. Sorting out these defective parts manually is a highly time-consuming and tedious process. An intelligent sorting system was developed based on machine vision using a Radial Basis Function (RBF) neural network learning algorithm in this study. First, a high-speed charge-coupled device camera was used to obtain a series of images of perfect and defective block bamboo parts. Next, the RBF neural-network learning algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Firstly, a camera was used to acquire the image of the item to be sorted, then RBF neural network algorithm was used to acquire the defective features in the image and localize the features, and finally an air jet was designed to extrude the defective items from the conveyor belt. The performance of the whole system was tested and it was found that the system has a high removal rate of 91.7% for defective items 25 . To facilitate port automation, Miao et al proposed a 3D point cloud hull modeling and operational target recognition algorithm based on a laser measurement collection system.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, a camera was used to acquire the image of the item to be sorted, then RBF neural network algorithm was used to acquire the defective features in the image and localize the features, and finally an air jet was designed to extrude the defective items from the conveyor belt. The performance of the whole system was tested and it was found that the system has a high removal rate of 91.7% for defective items 25 . To facilitate port automation, Miao et al proposed a 3D point cloud hull modeling and operational target recognition algorithm based on a laser measurement collection system.…”
Section: Discussionmentioning
confidence: 99%
“…The performance of the system was examined and found to have a classification time of only 0.002 s for faulty images. Liu et al 31 developed an intelligent sorting system based on machine vision using neural network algorithms. First, a camera was used to acquire the image of the item to be sorted, then RBF neural network algorithm was used to acquire the defective features in the image and localize the features, and finally an air jet was designed to extrude the defective items from the conveyor belt.…”
Section: Discussionmentioning
confidence: 99%
“…Based on machine vision technology, Wang et al (2021c) carried out extreme learning machine ELM to classify the color of solid wood floor, and used three different algorithms, namely grey wolf optimization (GWO), genetic optimization (GA), and particle swarm optimization (PSO), to optimize and compare their recognition efficiency and accuracy, providing an effective solution for the online intelligent sorting of solid wood floor color in household enterprises. Liu et al (2018) applied the machine vision to the automatic color sorting system of bamboo slice. Through the machine vision to analyze, process and extract the color characteristics of bamboo slices, and combined with the pattern recognition algorithm to design the sorting system, the rapid sorting of bamboo slices was finally achieved.…”
Section: Surface Color Analysis Of Wood Productsmentioning
confidence: 99%